Estressores agudos distintos produzem diferentes magnitudes do comportamento tipo de ansiedade e liberação diferencial de glutamato no cérebro de zebrafish - MARTINS, Milena Letícia (Universidade Federal do Pará, 2025)
Anxiety disorder is one of the most well characterized behavioral disorder in individuals submitted to acute or chronic stress. However, few studies have demonstrated how different types of stressors can modulate the neurochemical alterations involved in generation of anxiety. In the present study, we hypothesize that subjects exposed to different aversive stimuli (mechanical, chemical and spatial restriction) present varied intensity of anxiety-like behavior response associated with distinct pattern of GABA and Glutamate release in the brain. Sixty adult Danio rerio animals were randomly divided into four experimental groups: Control (CTRL), Acute Restraint Stress (ARS), Conspecific Alarm Substance (CAS) and Chasing with Net (CN). After applying the stress protocols, the animals were individually transferred to the Novel Tank Diving Test for behavioral analysis. Subsequently, their brains were collected and subjected to GABA and Glutamate release assay for quantification by HPLC. Our behavioral results showed that all aversive stimuli were capable of inducing anxiety-like behavior. However, the impact of anxiogenic behavior was more prominent in the CN and CAS groups when compared to ARS. This phenomenon was evident in all analyzed behavioral parameters (time on top, freezing, mean speed, maximum speed and erratic swimming). Our data also have shown that all aversive stimuli induced significant decrease in GABA release when compared to the control group. On the other side, only animals exposed to CN and CAS presented increase in extracellular glutamate levels. Different acute stressors induce different intensity of Anxiety-like behavior in zebrafish as well as they provoke specific alterations on the GABAerigic and Glutamatergic release in the brain. These results demonstrate the complexity of anxiety disorders, highlighting that both behavioral and neurochemical responses are highly context-dependent, supporting our initial hypothesis.